Effect of Pioglitazone on Cardiovascular Outcome in Diabetes and Chronic Kidney Disease - Christian Schneider; Ele Ferrannini; Ralph A. DeFronzo; Guntram Schernthaner; John Yates; Erland Erdmann (2007)
Patients with diabetes and chronic kidney disease (CKD) are at particularly high risk for cardiovascular disease (CVD). This post hoc analysis from the PROspective pioglitAzone Clinical Trial In macroVascular Events (PROactive) investigated the relationship between CKD and incident CVD in a population of patients with diabetes and documented macrovascular disease, as well as the effects of pioglitazone treatment on recurrent CVD. CKD, defined as an estimated GFR <60 ml/min per 1.73m(2), was present in 597 (11.6%) of 5154 patients. More patients with CKD reached the primary composite end point (all-cause mortality, myocardial infarction (MI), stroke, acute coronary syndrome, coronary/carotid arterial intervention, leg revascularization, or amputation above the ankle) than patients without CKD (27.5 versus 19.6%; P < 0.0001). Patients with CKD were also more likely to reach a secondary composite end point (all-cause mortality, MI, and stroke). Patients who had CKD and were treated with pioglitazone were less likely to reach the secondary end point (hazard ratio 0.66; 95% confidence interval 0.45 to 0.98), but this association was not observed among those with better renal function. In addition, there was a greater decline in estimated GFR with pioglitazone (between-group difference 0.8 ml/min per 1.73 m(2)/yr) than with placebo. In conclusion, CKD is an independent risk factor for cardiovascular events and death among patients with diabetes and preexisting macrovascular disease. Patients who had CKD and were treated with pioglitazone were less likely to reach a composite end point of all-cause death, MI, and stroke, independent of the severity of renal impairment.